Human Resource Management Strategy to Strengthen the Quality of Islamic Boarding School Education - Jafar Syahbuddin Ritonga (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
quality of education at the Darul Mursyid Islamic Boarding School. The research approach used is qualitative with a case study design, involving observation, in-depth interviews, and documentation studies. The results of the study indicate that despite challenges in terms of limited budget, facilities, and variations in formal qualifications of educators, effective HRM has had a positive impact on the quality of education. The implementation of structured HRM and the principle of open communication between Islamic boarding school managers and educators creates a conducive educational environment, increases educator motivation, and strengthens the quality of teaching. Although most of the training is informal, the efforts of Islamic boarding school managers to provide coaching through mentoring have proven effective. This study also suggests increasing formal training, more routine professional development, and utilizing technology in learning as steps to further improve the quality of education. With these recommendations, it is hoped that the quality of education at the Darul Mursyid Islamic Boarding School can continue to develop and be relevant to the times.